Sustainability of rights after globalisation - Basu Ray Chaudhury, Sabyasachi; Dey, Ishita, 1982-; Sage eBooks (Los Angeles ; London : SAGE, 2011)
As the news tells us every day, people across the world have been fighting their clause for human rights and finding a platform on an increasingly global scale. For India, this is a gradually growing issue, as discussed and explored in this exciting new title.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Natural resources, Communal -- India -- Management; Commons -- India -- Case studies; Globalization -- Social aspects; Globalization -- Political aspects; India -- Politics and government; Electronic books